Systemic inflammation impairs microglial Aβ clearance through NLRP3 inflammasome. (30th July 2019) - Tejera, Dario; Mercan, Dilek; Sanchez‐Caro, Juan M; Hanan, Mor; Greenberg, David; Soreq, Hermona; Latz, Eicke; Golenbock, Douglas; Heneka, Michael T
Abstract: Alzheimer's disease is the most prevalent type of dementia and is caused by the deposition of extracellular amyloid‐beta and abnormal tau phosphorylation. Neuroinflammation has emerged as an additional pathological component. Microglia, representing the brain's major innate immune cells, play an important role during Alzheimer's. Once activated, microglia show changes in their morphology, characterized by a retraction of cell processes. Systemic inflammation is known to increase the risk for cognitive decline in human neurogenerative diseases including Alzheimer's. Here, we assess for the first time microglial changes upon a peripheral immune challenge in the context of aging and Alzheimer's in vivo, using 2‐photon laser scanning microscopy. Microglia were monitored at 2 and 10 days post‐challenge by lipopolysaccharide. Microglia exhibited a reduction in the number of branches and the area covered at 2 days, a phenomenon that resolved at 10 days. Systemic inflammation reduced microglial clearance of amyloid‐beta in APP/PS1 mice. NLRP3 inflammasome knockout blocked many of the observed microglial changes upon lipopolysaccharide, including alterations in microglial morphology and amyloid pathology. NLRP3 inhibition may thus represent a novel therapeutic target that may protect the brain from toxic peripheral inflammation during systemic infection. Synopsis: Microglia morphology and Aβ clearance is negatively regulated by systemic inflammation in a NLRP3‐dependent fashion. Collectively, these results shed light on the mechanism underlying Alzheimer disease progress and aggravation upon peripheral inflammation. Systemic inflammation activates microglia in a transient and NLRP3‐dependent manner. Systemic inflammation impairs amyloid‐beta microglial clearance. APP/PS1 but not APP/PS1xNLRP3ko mice show accelerated amyloid‐beta deposition upon systemic immune challenge. Collectively these data suggest that NLRP3 inhibition may protect from peripheral inflammation driven aggravation of cerebral amyloidosis. Abstract : Microglia morphology and Aβ clearance is negatively regulated by systemic inflammation in a NLRP3‐dependent manner.